2021
DOI: 10.1097/prs.0000000000008527
|View full text |Cite
|
Sign up to set email alerts
|

Female Leadership in Academic Plastic Surgery: A Comprehensive Analysis

Abstract: Background: Gender equity remains to be realized in academic plastic and reconstructive surgery. The purpose of this study was to measure the proportion of women in leadership roles in academic plastic and reconstructive surgery to verify where gender gaps may persist. Methods: Six markers of leadership were analyzed: academic faculty rank, manuscript authorship, program directorship, journal editor-in-chief positions, society board of directors membership, and professional society membership. Descriptive stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…24 A review of the five plastic surgery journals with the highest impact factor found that none had a female editor-in-chief. 20 These statistics highlight the disparity that continues to exist, and the importance we must place on supporting women in the field.…”
Section: Gender Imbalance Persistsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 A review of the five plastic surgery journals with the highest impact factor found that none had a female editor-in-chief. 20 These statistics highlight the disparity that continues to exist, and the importance we must place on supporting women in the field.…”
Section: Gender Imbalance Persistsmentioning
confidence: 99%
“…In addition, this study reported that nineteen institutions had no female faculty. 20 A study of invited speakers at five academic plastic surgery meetings in 2017 found that women comprised a minority of invited speakers at academic plastic surgery meetings, despite the fact that the impact of women's published work was no different than that of men among the junior and midcareer faculty. 21 Studies of authorship in the plastic surgery literature have noted women in the minority of first author and senior author publications.…”
Section: Gender Imbalance Persistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant literature confirmed that, although there has been progress for women in medicine (Joseph et al, 2021), the gender gap is still present in healthcare sector and is rooted in gender biases and gender norms that date back thousands of years (Newman et al 2020). In such a direction, several authors shed light on the fact that different fields of medicine, including paediatrics (Spector et al, 2019), emergency medicine (Ravioli et al, 2022), and plastic surgery (Moeller et al, 2021), is not leading the way in gender equity.…”
Section: Gender Equity In Hospitals: Still a Long Way To Gomentioning
confidence: 99%
“…There is a growing body of literature on personal characteristics and motivations of individuals becoming chairs in other medical specialties, as well as data on gender and race. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 It is well known that by virtue of its position at the cusp of basic science and clinical medicine, academic pathology departments embrace a wide range of clinical and research missions. The leadership required to steer these departments in the appropriate directions therefore must be equally diverse, encompassing basic scientists, physician scientists, and clinical practitioners bolstered by diversity in race, gender and leadership qualifications.…”
Section: Introductionmentioning
confidence: 99%